2013
DOI: 10.1186/2196-1042-14-30
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation accelerates orthodontic alignment in the early phase of treatment

Abstract: BackgroundNumerous strategies have been proposed to decrease the treatment time a patient requires in orthodontic treatment. Recently, a number of device-accelerated therapies have emerged in orthodontics. Photobiomodulation is an emerging area of science that has clinical applications in a number of human biological processes. The aim of this study was to determine if photobiomodulation reduces the treatment time in the alignment phase of orthodontic treatment.MethodsThis multicenter clinical trial was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 38 publications
1
70
0
1
Order By: Relevance
“…The results of the present study concluded that low level laser had stimulatory effect on acceleration of orthodontic tooth movement agreed with the findings which were reported by many human studies (3,11,12,13,14,15,16,17,18,19) and disagreed with other studies which showed no effect on tooth movement (20,21,22) . This controversial results in the previous studies may be due to the different energy densities they used; which mentioned in Arndt-Schulz law; who stated that low doses have stimulatory and high dosages have inhibitory effects (23) or may be due to the longer wavelengths they used (8) .…”
Section: Discussionsupporting
confidence: 73%
“…The results of the present study concluded that low level laser had stimulatory effect on acceleration of orthodontic tooth movement agreed with the findings which were reported by many human studies (3,11,12,13,14,15,16,17,18,19) and disagreed with other studies which showed no effect on tooth movement (20,21,22) . This controversial results in the previous studies may be due to the different energy densities they used; which mentioned in Arndt-Schulz law; who stated that low doses have stimulatory and high dosages have inhibitory effects (23) or may be due to the longer wavelengths they used (8) .…”
Section: Discussionsupporting
confidence: 73%
“…Previous PBM studies [34,35,[37][38][39][40] have shown an improvement rate of 0-30% for cases treated with PBM. The calculation of the sample size was based on these assumptions: & Outcome variable: The rate of monthly space closure will be measured by taking the total space closed between T2 and T1, divided by the time elapsed in months.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Accelerated tooth movement had a fast evolution; it has a variety of approaches that includes surgical techniques and no surgical modalities [2], such as micro vibration [3], light stimulation [4], pharmacological approaches [5], etc. The surgical facilitated orthodontic treatment protocol is very popular and different authors have established a particular sequence of procedures or speci ic steps to name, rename or patent a particular technique, for example: Wilckodontics (OAO TM ) [6][7][8][9][10], Piezosurgery [11], Piezocision [12], Speedy orthodontics [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment objectives for this case were to [1], eliminate dental crowding [2], achieve better facial balance [3], maintain a Class I dental relationship [4] maintain the root length of the teeth.…”
Section: Treatment Objectivesmentioning
confidence: 99%